Freezing point cracking resistant fuel cell catalyst layer, CCM and preparation method thereof
By alternately stacking carbon nanotube-supported catalysts and conventional carbon-supported catalysts in the fuel cell catalytic layer, the problem of prone to cracking in the freezing point of the traditional catalytic layer is solved, and higher durability and flexibility are achieved.
Patent Information
- Application Number
- CN202411733611.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
The catalytic layer of traditional fuel cell is prone to repeated volume changes due to the expansion and melting of water at freezing point, which in turn causes cracking of the catalytic layer and affects the durability of CCM.
By alternately stacking carbon nanotube-supported catalysts and conventional carbon-supported catalysts in the fuel cell catalytic layer, the flexibility of the catalyst layer is improved, slight deformation is buffered, and cracked.
On the premise of retaining conventional catalytic functions, the flexibility of the fuel cell catalytic layer is improved, the slight deformation of the catalytic layer is reduced, and the catalytic layer is effectively resisted cracking, thereby improving the durability of CCM.
Smart Images

Figure CN119518007A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a fuel cell catalyst layer resistant to freezing point cracking, a CCM and a preparation method thereof. Background Art
[0002] A fuel cell is a catalytic site that directly converts the chemical energy of a fuel into electrical energy. It has high energy conversion efficiency and low pollution, and is an ideal power source for the future. Among them, CCM (Catalyst coated Membrane) is the workplace where the fuel cell undergoes electrochemical reactions and generates electrical energy, and plays a major role in the performance and life of the fuel cell. The catalytic layer in the CCM is the site of the electrochemical reaction and plays a key role in the process of converting chemical energy into electrical energy.
[0003] Traditional fuel cells have a complex structure, multiple interfaces, and abundant pores in their catalyst layers. The water generated during operation is very unevenly distributed. During the shutdown purge phase, it is impossible to quickly remove water from some dead corners, especially the residual water in the pores of the catalyst layer. When the fuel cell encounters low temperatures after operation, these residual water will form ice crystals at temperatures below freezing, expand in volume, and the catalyst layer will be squeezed by the expansion of ice crystals; when the fuel cell is heated above freezing, the ice crystals melt, and the squeezing force on the catalyst layer disappears. When the fuel cell experiences repeated temperature changes above and below the freezing point, the formation and melting of ice crystals will occur repeatedly in the water accumulation area of the catalyst layer, resulting in repeated volume changes. Repeated volume changes cause the catalyst layer to be repeatedly squeezed. Long-term squeezing force will cause the catalyst layer to crack and deform, ultimately affecting the durability of the CCM.
[0004] The carbon carriers of conventional Pt / C catalysts are mostly Ketjen black and Vulcan carbon, which have low flexibility and the resulting catalytic layer has low toughness. When the CCM prepared by this method freezes below freezing point, the catalytic layer has little buffering effect against extrusion and is prone to cracking. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a fuel cell catalyst layer, CCM and a preparation method thereof that are resistant to freezing point cracking. By alternately stacking conventional catalyst layers and carbon nanotube catalyst layers, the flexibility of the entire catalyst layer is improved, the micro-deformation of the catalyst layer is reduced, and the catalyst layer cracking is resisted.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A first aspect of the present invention provides a fuel cell catalyst layer resistant to freezing point cracking, the fuel cell catalyst layer comprising a first catalyst layer and a second catalyst layer alternately stacked;
[0008] The components of the first catalytic layer include a carbon-supported catalyst, wherein the carbon-supported catalyst includes a carbon support and a first metal catalyst supported on the carbon support;
[0009] The components of the second catalytic layer include a carbon nanotube-supported catalyst, and the carbon nanotube-supported catalyst includes a carbon nanotube carrier and a second metal catalyst supported on the carbon nanotube carrier.
[0010] Preferably, in the carbon-supported catalyst, the mass percentage of the first metal catalyst is 15 to 75%; and / or
[0011] In the carbon nanotube-supported catalyst, the mass percentage of the second metal catalyst is 30% to 75%.
[0012] Preferably, the first metal catalyst and / or the second metal catalyst is platinum or a platinum alloy catalyst.
[0013] Preferably, the components of the first catalytic layer further include: deionized water, ion resin and organic solution; and / or
[0014] The components of the second catalytic layer also include: deionized water, ion resin and organic solution.
[0015] Preferably, the organic solution is alcohol, ether, ester or ketone with 1 to 10 carbon atoms.
[0016] Preferably, the mass percentage of the carbon-supported catalyst in the components of the first catalytic layer is 25-50%; and / or
[0017] Among the components of the second catalytic layer, the mass percentage of the carbon nanotube-supported catalyst is 18% to 40%.
[0018] Preferably, the single layer height of the first catalytic layer and the second catalytic layer is 1 to 7 microns.
[0019] A second aspect of the present invention provides a CCM, comprising a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer located on both sides of the proton exchange membrane, wherein the anode catalyst layer and / or the cathode exchange membrane adopts the aforementioned fuel cell catalyst layer.
[0020] Preferably, in the anode catalyst layer, the number of layers of the first catalyst layer and the second catalyst layer is 1 to 5; and / or
[0021] In the cathode catalyst layer, the number of layers of the first catalyst layer and the second catalyst layer is 1 to 5.
[0022] A third aspect of the present invention provides a method for preparing a fuel cell catalyst layer, comprising:
[0023] providing a first catalyst slurry, wherein components of the first catalyst slurry include a carbon-supported catalyst;
[0024] Providing a second catalyst slurry, wherein the components of the second catalyst slurry include a carbon nanotube-supported catalyst;
[0025] The first catalyst slurry and the second catalyst slurry are used to form a first catalyst layer and a second catalyst layer that are alternately stacked on a substrate.
[0026] Preferably, providing the first slurry comprises:
[0027] Adding the carbon-supported catalyst, deionized water, ion resin and organic solution into a first container and performing a first stirring;
[0028] Ultrasonic dispersion is performed on the stirred solution;
[0029] The ultrasonically dispersed solution was stirred a second time.
[0030] Preferably, the first stirring time is 5 to 120 minutes, the ultrasonic dispersion time is 1 to 30 minutes, and the second stirring time is 5 to 120 minutes.
[0031] Preferably, providing the second slurry comprises:
[0032] Adding the carbon nanotube-supported catalyst, deionized water, ion resin and organic solution into a second container and performing a first stirring;
[0033] Ultrasonic dispersion is performed on the stirred solution;
[0034] The ultrasonically dispersed solution was stirred a second time.
[0035] Preferably, the first stirring time is 5 to 120 minutes, the ultrasonic dispersion time is 1 to 30 minutes, and the second stirring time is 5 to 120 minutes.
[0036] The fourth aspect of the present invention provides a method for preparing a CCM, comprising providing an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane, disposing the anode catalyst layer on one side of the proton exchange membrane, and disposing the cathode catalyst layer on the other side of the proton exchange membrane, wherein the anode catalyst layer and / or the cathode catalyst layer are provided according to the method for preparing a fuel cell catalyst layer as described above.
[0037] By adopting the above technical solution, the present invention has the following beneficial effects:
[0038] The present invention alternately layers carbon nanotube-loaded catalysts and conventional carbon-loaded catalysts in a fuel cell catalyst layer. Since carbon nanotubes are a conductive material with a certain toughness, their conductivity can meet the conductivity requirements of the catalyst layer. The second metal catalyst loaded thereon can provide catalytic activity. When the carbon nanotube-loaded catalysts are orderly distributed in the catalyst layer, their toughness can buffer the slight deformation of the catalyst layer. Thus, the fuel cell catalyst layer can resist cracking of the catalyst layer while retaining the conventional catalytic function, thereby improving the durability of the CCM. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the structure of the CCM prepared in Example 1 of the present invention;
[0040] Figure 2 This is a schematic diagram of the structure of the CCM prepared in Example 2 of the present invention;
[0041] Figure 3 Schematic diagram of the structure of CCM prepared in comparative example;
[0042] Figure 4A This is a microscopic change diagram of the CCM prepared in Example 1 of the present invention after 200 high and low temperature cycles;
[0043] Figure 4B This is a microscopic change diagram of the CCM prepared in Example 2 of the present invention after 200 high and low temperature cycles;
[0044] Figure 4C This is a microscopic change diagram of the CCM prepared in Example 3 of the present invention after 200 high and low temperature cycles. DETAILED DESCRIPTION
[0045] The embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0046] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.
[0047] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein can be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present application, it should be understood by those skilled in the art that an aspect described herein can be implemented independently of any other aspect, and two or more of these aspects can be combined in various ways. For example, any number and aspect described herein can be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein can be used to implement this device and / or practice this method.
[0048] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present application. The drawings only show components related to the present application rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0049] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the examples can be practiced without these specific details.
[0050] An embodiment of the present invention provides a fuel cell catalyst layer that is resistant to freezing point cracking, the catalyst layer comprising a first catalyst layer and a second catalyst layer that are alternately stacked; components of the first catalyst layer include a carbon-loaded catalyst, the carbon-loaded catalyst includes a carbon carrier and a first metal catalyst loaded on the carbon carrier; components of the second catalyst layer include a carbon nanotube-loaded catalyst, the carbon nanotube-loaded catalyst includes a carbon nanotube carrier and a second metal catalyst loaded on the carbon nanotube carrier.
[0051] Optionally, in the carbon-supported catalyst, the mass percentage of the first metal catalyst is 15-75%.
[0052] Optionally, in the carbon nanotube-supported catalyst, the mass percentage of the second metal catalyst is 30% to 75%.
[0053] Optionally, the first metal catalyst is platinum or a platinum alloy.
[0054] Optionally, the second metal catalyst is also platinum or a platinum alloy.
[0055] Optionally, in addition to the carbon-supported catalyst, the components of the first catalytic layer further include: deionized water, ion resin and organic solution.
[0056] Optionally, in addition to the carbon nanotube-supported catalyst, the components of the second catalytic layer further include: deionized water, ion resin and organic solution.
[0057] Optionally, the organic solution in the present application may be a mixture of one or more of alcohols, ethers, esters, and ketones having 1 to 10 carbon atoms.
[0058] Optionally, in the components of the first catalytic layer, the mass percentage of the carbon-supported catalyst is 25-50%.
[0059] Optionally, in the components of the second catalytic layer, the mass percentage of the carbon nanotube-supported catalyst is 18% to 40%.
[0060] In this embodiment, the first catalyst layer is a conventional fuel cell catalyst layer. In the first catalyst layer and the second catalyst layer, the ratio of deionized water, ion resin and alcohol solution can be configured according to the ratio of conventional fuel cell catalyst slurry.
[0061] Optionally, a single layer height of the first catalytic layer is 1 to 7 microns.
[0062] Optionally, the single layer height of the second catalytic layer is 1 to 7 microns.
[0063] The above-mentioned fuel cell catalyst layer is formed by alternately stacking carbon nanotube-loaded catalysts and conventional carbon-loaded catalysts. Since carbon nanotubes are a tough conductive material, when used to prepare the catalyst layer of the fuel cell catalyst, its toughness can buffer the slight deformation of the catalyst layer, thereby enabling the fuel cell catalyst layer to improve the flexibility of the entire catalyst layer while retaining the conventional catalytic function, reduce the slight deformation of the catalyst layer, and resist cracking of the catalyst layer.
[0064] Another embodiment of the present invention provides a CCM, which includes a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer located on both sides of the proton exchange membrane, wherein the anode catalyst layer and / or the cathode exchange membrane are implemented using the fuel cell catalyst layer as described above.
[0065] That is, in this embodiment, at least one of the anode catalyst layer and the cathode exchange membrane of the CCM includes a first catalyst layer and a second catalyst layer alternately stacked; wherein the components of the first catalyst layer include a carbon-loaded catalyst, the carbon-loaded catalyst includes a carbon carrier and a first metal catalyst loaded on the carbon carrier; the components of the second catalyst layer include a carbon nanotube-loaded catalyst, the carbon nanotube-loaded catalyst includes a carbon nanotube carrier and a second metal catalyst loaded on the carbon nanotube carrier.
[0066] Optionally, in the anode catalyst layer, the number of layers of the first catalyst layer and the second catalyst layer is 1 to 5.
[0067] Optionally, in the cathode catalyst layer, the number of layers of the first catalyst layer and the second catalyst layer is 1 to 5.
[0068] It should be understood that the present invention does not impose any specific restrictions on the single layer height and the total number of layers of the first catalytic layer and the second catalytic layer, and they can be designed according to actual needs.
[0069] At least one of the anode catalyst layer and the cathode catalyst layer of the above-mentioned CCM is arranged in an alternating manner by stacking carbon nanotube-loaded catalysts and conventional carbon-loaded catalysts. Since carbon nanotubes are a kind of tough conductive material, their conductivity can meet the conductivity requirements of the catalyst layer, and the second metal catalyst loaded thereon can provide catalytic activity. Since the carbon nanotube-loaded catalyst is orderly distributed in the catalyst layer, its toughness can at least partially offset the stress caused by the phase change of liquid water, so that the fuel cell catalyst layer can resist the cracking of the catalyst layer while retaining the conventional catalytic function, thereby improving the durability of the CCM and extending the life of the CCM.
[0070] Yet another embodiment of the present invention provides a fuel cell including the aforementioned CCM, thereby improving the durability performance of the fuel cell.
[0071] Another embodiment of the present invention provides a method for preparing a fuel cell catalyst layer, comprising the following steps:
[0072] S1, providing a first catalyst slurry, wherein the components of the first catalyst slurry include a carbon-supported catalyst;
[0073] S2, providing a second catalyst slurry, wherein the components of the second catalyst slurry include a carbon nanotube-supported catalyst;
[0074] S3, using the first catalyst slurry and the second catalyst slurry to form a first catalyst layer and a second catalyst layer alternately stacked on the substrate.
[0075] Optionally, step S1 provides a first catalyst slurry by the following steps:
[0076] Adding a carbon-supported catalyst, deionized water, an ion resin and an organic solution into a first container and performing a first stirring, wherein the first stirring time is 5 minutes to 120 minutes;
[0077] The stirred solution is ultrasonically dispersed for 5 to 120 minutes;
[0078] The ultrasonically dispersed solution is stirred for the second time, and the duration of the second stirring is 5 minutes to 120 minutes.
[0079] Optionally, step S2 provides a second catalyst slurry by the following steps:
[0080] Adding the carbon nanotube-supported catalyst, deionized water, ion resin and organic solution into the second container and performing a first stirring, wherein the first stirring time is 5 minutes to 120 minutes;
[0081] The stirred solution is ultrasonically dispersed for 5 to 120 minutes;
[0082] The ultrasonically dispersed solution is stirred for the second time, and the duration of the second stirring is 5 minutes to 120 minutes.
[0083] The above-mentioned method for preparing the fuel cell catalyst layer is carried out by alternately stacking carbon nanotube-loaded catalysts and conventional carbon-loaded catalysts. Since carbon nanotubes are a tough conductive material, their toughness can at least partially offset the stress caused by the phase change of liquid water, thereby enabling the fuel cell catalyst layer to buffer and offset stress concentration while retaining the conventional catalytic function.
[0084] Another embodiment of the present invention provides a method for preparing CCM, which specifically comprises the following steps:
[0085] Providing an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane, wherein the anode catalyst layer and / or the cathode catalyst layer is provided according to the above-mentioned preparation method of the fuel cell catalyst layer;
[0086] The anode catalyst layer is arranged on one side of the proton exchange membrane, and the cathode catalyst layer is arranged on the other side of the proton exchange membrane.
[0087] The above-mentioned method for preparing CCM prepares the anode catalyst layer and the cathode catalyst layer according to the above-mentioned method for preparing the fuel cell catalyst layer, so that the prepared CCM has better durability and longer service life.
[0088] The scheme of the present invention is further illustrated below in conjunction with specific embodiments and comparative examples.
[0089] Example 1
[0090] Step 1, prepare the first catalyst slurry:
[0091] Add 0.1000 g of 60% Pt / C (carbon-supported platinum) catalyst, 1.0000 g of deionized water, 0.1600 g of DE2020 ion resin, and 3.5 g of ethanol into a clean glass bottle, stir evenly with a magnetic stirrer, ultrasonically disperse for 5 minutes, and then continue stirring with a magnetic stirrer for 30 minutes for standby use.
[0092] Step 2, preparing the second catalyst slurry:
[0093] Add 0.0570 g of 30% Pt / CNT (carbon nanotube-supported platinum) catalyst, 1.0000 g of deionized water, 0.1600 g of DE2020 ion resin, and 3.5 g of ethanol into a clean glass bottle, stir evenly with a magnetic stirrer, ultrasonically disperse for 5 minutes, and then continue stirring with a magnetic stirrer for 30 minutes for standby use.
[0094] Step 3: Preparation of cathode catalyst layer
[0095] The first catalyst slurry is ultrasonically sprayed on the PTFE substrate, and the required loading is controlled to form a first catalytic layer Ca1; the second catalyst slurry is ultrasonically sprayed on the first catalytic layer Ca1, and the required loading is controlled to form a second catalytic layer Cb1; the first catalyst slurry is ultrasonically sprayed on the second catalytic layer Cb1, and the required loading is controlled to form a first catalytic layer Ca2; the first catalyst slurry is ultrasonically sprayed on the first catalytic layer Ca2, and the required loading is controlled to form a first catalytic layer Ca3.
[0096] Step 4: Preparation of anode catalyst layer
[0097] The first catalyst slurry is ultrasonically sprayed on the PTFE substrate, and the required loading is controlled to form a first catalytic layer Aa1; the first catalyst slurry is ultrasonically sprayed on the first catalytic layer Aa1, and the required loading is controlled to form a first catalytic layer Aa2.
[0098] Step 5. Prepare CCM
[0099] The prepared cathode catalyst layer was disposed on one side of the proton exchange membrane, and the prepared anode catalyst layer was disposed on the other side of the proton exchange membrane to prepare a catalyst coated membrane (CCM), which was recorded as CCM-1.
[0100] The CCM-1 prepared in this example is as follows Figure 1 As shown, the anode catalyst layer adopts a single catalyst layer of Aa1+Aa1; the cathode catalyst layer adopts a composite catalyst layer of Ca1+Cb1+Ca2+Ca3 prepared by spraying the first catalyst slurry and the second catalyst slurry.
[0101] Example 2
[0102] Step 1 is the same as Step 1 of Example 1, preparing a first catalyst slurry.
[0103] Step 2 is the same as Step 2 of Example 1, preparing a second catalyst slurry.
[0104] Step 3: Preparation of cathode catalyst layer
[0105] The first catalyst slurry is ultrasonically sprayed on the PTFE substrate, and the required loading is controlled to form a first catalytic layer Ca1; the second catalyst slurry is ultrasonically sprayed on the first catalytic layer Ca1, and the required loading is controlled to form a second catalytic layer Cb1; the first catalyst slurry is ultrasonically sprayed on the second catalytic layer Cb1, and the required loading is controlled to form a first catalytic layer Ca2; the second catalyst slurry is ultrasonically sprayed on the first catalytic layer Ca2, and the required loading is controlled to form a second catalytic layer Cb2.
[0106] Step 4 is the same as step 4 of Example 1, to prepare an anode catalyst layer.
[0107] Step 5 is the same as step 5 of Example 1 to prepare a catalyst coated membrane, which is denoted as CCM-2.
[0108] The CCM-2 prepared in this example is as follows Figure 2 As shown, the anode catalyst layer adopts a single catalyst layer of Aa1+Aa1; the cathode catalyst layer adopts a composite catalyst layer of Ca1+Cb1+Ca2+Cb2 prepared by spraying the first catalyst slurry and the second catalyst slurry.
[0109] Comparative Example
[0110] Step 1 is the same as Step 1 of Example 1, preparing a first catalyst slurry.
[0111] Step 2: Preparation of cathode catalyst layer
[0112] Four layers of the first catalyst slurry are ultrasonically sprayed on the PTFE substrate, and the required loading is controlled to form four first catalyst layers Ca1-Ca4.
[0113] Step 3 is the same as step 4 of Example 1 and Example 2, and an anode catalyst layer is prepared.
[0114] Step 4 is the same as step 5 of Example 1 and Example 2, and a catalyst coated membrane is prepared, which is denoted as CCM-3.
[0115] The CCM-3 prepared in this example is as follows Figure 3 As shown, its anode catalyst layer adopts a single catalyst layer of Aa1+Aa1; its cathode catalyst layer adopts a single catalyst layer of Ca1+Ca2+Ca3+Ca4.
[0116] In order to verify the deformation buffering effect of the catalyst layer structure of the present invention, the CCM prepared according to the above specific embodiments and comparative examples was treated by high and low temperature alternating cycles, and the effects were compared by comparing the microscopic changes before and after the CCM treatment offline.
[0117] During the specific test, each CCM (CCM-1, CCM-2, CCM-3) was placed in a high and low temperature cycle test chamber, and the temperature range was set to (-20±1℃~20±1℃) for testing. The test steps are as follows:
[0118] 1. Each CCM (CCM-1, CCM-2, CCM-3) prepared in each embodiment and comparative example was cut into 2 cm*2 cm strips, placed in a closed environment with 100% humidity and temperature of 20±1°C for 1 hour, and then 3 cm*3 cm carbon paper was attached to both sides of each CCM and clamped with a clamp.
[0119] 2. Place the above fixture in a -20±1℃ environmental chamber for 1 hour.
[0120] 3. Remove the clamp and quickly restore the temperature to 20±1℃ and maintain it for 1 hour.
[0121] 4. Repeat steps 2 to 3 above to complete a cycle, and repeat this cycle 200 times.
[0122] 5. Open the fixture, take out each CCM, and observe the surface morphology changes using an electron microscope. The microscopic changes of CCM-1 after 200 high and low temperature cycles are as follows: Figure 4A As shown; the microscopic changes of CCM-2 after 200 high and low temperature cycles are shown Figure 4B As shown; the microscopic changes of CCM-3 after 200 high and low temperature cycles are shown Figure 4C shown.
[0123] By comparison, it can be seen that the microscopic changes of CCM-2 prepared in Example 2 are the smallest, and the microscopic changes of CCM-3 prepared in the comparative example are the largest. It can be seen that the CCM obtained according to the present invention is more resistant to cracking of the catalyst layer under high and low temperature cycles.
[0124] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A fuel cell catalyst layer resistant to freezing point cracking, characterized in that: The fuel cell catalyst layer comprises a first catalyst layer and a second catalyst layer which are alternately stacked; The components of the first catalytic layer include a carbon-supported catalyst, wherein the carbon-supported catalyst includes a carbon support and a first metal catalyst supported on the carbon support; The components of the second catalytic layer include a carbon nanotube-supported catalyst, and the carbon nanotube-supported catalyst includes a carbon nanotube carrier and a second metal catalyst supported on the carbon nanotube carrier.
2. The fuel cell catalyst layer according to claim 1, characterized in that: In the carbon-supported catalyst, the mass percentage of the first metal catalyst is 15 to 75%; In the carbon nanotube-supported catalyst, the mass percentage of the second metal catalyst is 30% to 75%.
3. The fuel cell catalyst layer according to claim 1, characterized in that: The first metal catalyst and / or the second metal catalyst is platinum or a platinum alloy.
4. The fuel cell catalyst layer according to claim 1, characterized in that: The components of the first catalytic layer also include: deionized water, ion resin and organic solvent; and / or The components of the second catalytic layer also include: deionized water, ion resin and organic solution.
5. The fuel cell catalyst layer according to claim 4, characterized in that: The organic solution is alcohol, ether, ester or ketone.
6. The fuel cell catalyst layer according to claim 4, characterized in that: Among the components of the first catalytic layer, the mass percentage of the carbon-supported catalyst is 25-50%; and / or Among the components of the second catalytic layer, the mass percentage of the carbon nanotube-supported catalyst is 18% to 40%.
7. The fuel cell catalyst layer according to claim 1, characterized in that: The single layer height of the first catalytic layer and / or the second catalytic layer is 1 to 7 microns.
8. A CCM comprising a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer located on both sides of the proton exchange membrane, characterized in that: The anode catalyst layer and / or the cathode exchange membrane adopts the fuel cell catalyst layer as claimed in any one of claims 1 to 7.
9. The CCM of claim 8, wherein: In the anode catalyst layer, the number of layers of the first catalyst layer and the second catalyst layer is 1 to 5; and / or In the cathode catalyst layer, the number of layers of the first catalyst layer and the second catalyst layer is 1 to 5.
10. A method for preparing a fuel cell catalyst layer, characterized in that: include: providing a first catalyst slurry, wherein components of the first catalyst slurry include a carbon-supported catalyst; Providing a second catalyst slurry, wherein the components of the second catalyst slurry include a carbon nanotube-supported catalyst; The first catalyst slurry and the second catalyst slurry are used to form a first catalyst layer and a second catalyst layer that are alternately stacked on a substrate.
11. The method for preparing a fuel cell catalyst layer according to claim 10, characterized in that: Providing the first slurry comprises: Adding the carbon-supported catalyst, deionized water, ion resin and organic solution into a first container and performing a first stirring; Ultrasonic dispersion is performed on the stirred solution; The ultrasonically dispersed solution was stirred a second time.
12. The method for preparing a fuel cell catalyst layer according to claim 11, characterized in that: The first stirring time is 5 to 120 minutes, the ultrasonic dispersion time is 1 to 30 minutes, and the second stirring time is 5 to 120 minutes.
13. The method for preparing a fuel cell catalyst layer according to claim 10, characterized in that: Providing the second slurry comprises: Adding the carbon nanotube-supported catalyst, deionized water, ion resin and organic solution into a second container and performing a first stirring; Ultrasonic dispersion is performed on the stirred solution; The ultrasonically dispersed solution was stirred a second time.
14. The method for preparing a fuel cell catalyst layer according to claim 13, characterized in that: The first stirring time is 5 to 120 minutes, the ultrasonic dispersion time is 1 to 30 minutes, and the second stirring time is 5 to 120 minutes.
15. A method for preparing a CCM, comprising providing an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane, disposing the anode catalyst layer on one side of the proton exchange membrane, and disposing the cathode catalyst layer on the other side of the proton exchange membrane, characterized in that: The anode catalyst layer and / or the cathode catalyst layer is provided according to the method for preparing a fuel cell catalyst layer according to any one of claims 10-14.